Caracterización genética y patrones de resistencia antimicrobiana en cepas de Salmonella enterica subsp. enterica serovar Typhimurium en cuyes de crianza intensiva - Huamán, Meylin (2020)
The aim of this study was to conduct a phenotypic and genetic characterization of 35 Salmonella Typhimurium isolates from guinea pig production systems in the Lima, Peru in relation to antimicrobial resistance. The profile of 11 antibiotics (florfenicol, sulfamethoxazole, doxycycline, oxytetracycline, amoxicillin, enrofloxacin, norfloxacin, levofloxacin, ciprofloxacin, colistin and fosfomycin), genotyping by ERIC-PCR techniques and quinolone resistance gene profile (qnrB, qnRD, qnRD, qnrD, qnrD , aa6), tetracyclines (tetA, tetB, tetC, tetD), phenols (cat1, cat2, cmlA, cmlB) and sulfamethoxazole (sul1, sul2). The results indicate the presence of multidrug resistance in 80% (n=28) of the strains, being the most common resistance to the antibiotic colistin (91.4%), followed by sulfamethoxazole (68.6%) and enrofloxacin (62.9%), and with a moderate resistance to amoxicillin (20%), ciprofloxacin (20%) and norfloxacin (11.43%). Nine of 14 resistance genes were detected, with a higher frequency of the tetB genes (71.4%), sulI (57.1%) and cat2 (48.6%). The presence of seven differentiated genetic profiles (A-G) distributed in two genetic clusters was observed, the most frequent was the D profile (54.3%) followed by the C profile (28.6%). The results suggest the presence of Salmonella Typhimurium strains with moderate variability and multidrug resistance profiles with the presence of resistance genes, mainly for tetracyclines and sulfonamides.